2010
DOI: 10.1016/j.jinorgbio.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of the zinc sensor FluoZin-3 with Zn7-metallothionein: Inquiry into the existence of a proposed weak binding site

Abstract: It has been reported that Zn7-metallothionein (MT), contains one weak binding site for Zn2+. To test this conclusion, rabbit liver MT isolated at pH 7 was reacted with chelating agents of modest affinity for Zn2+. Contrary to the previous study, no evidence was found for Zn2+ stoichiometically bound to the protein with an apparent stability constant of about 108. Indeed, stability constant measurements based upon competition between Zn7-MT and ligands of known stability with Zn2+ showed that all of the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…It does compete for much of the adventitiously bound Zn 2+ to form Zn(ZQ) 2 and also appears to bind the rest in the form of ternary complexes, which are revealed by a blue-shift in the fluorescence emission spectrum of Zn(ZQ) 2 from 490 nm to 470 nm [19]: normalZnormalnproteomenormalZnormaln+2normalZnormalQnormalZnormalQnormalZnormalnproteomenormalZnormalnnormalZnormalQ Also, as documented in previous studies and below in Figure 5a, 4 μM apometallothionein, which provided 28 μM in Zn 2+ binding sites, removed little if any Zn 2+ from 28 μM Zn-proteome to form Zn-MT [21,22]. Thus, as with ZQ, Zn-proteome is mostly unreactive with an endogenous ligand, apo-MT, that also has a large binding constant for Zn 2+ , 10 11.2 [16]. …”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…It does compete for much of the adventitiously bound Zn 2+ to form Zn(ZQ) 2 and also appears to bind the rest in the form of ternary complexes, which are revealed by a blue-shift in the fluorescence emission spectrum of Zn(ZQ) 2 from 490 nm to 470 nm [19]: normalZnormalnproteomenormalZnormaln+2normalZnormalQnormalZnormalQnormalZnormalnproteomenormalZnormalnnormalZnormalQ Also, as documented in previous studies and below in Figure 5a, 4 μM apometallothionein, which provided 28 μM in Zn 2+ binding sites, removed little if any Zn 2+ from 28 μM Zn-proteome to form Zn-MT [21,22]. Thus, as with ZQ, Zn-proteome is mostly unreactive with an endogenous ligand, apo-MT, that also has a large binding constant for Zn 2+ , 10 11.2 [16]. …”
Section: Resultsmentioning
confidence: 77%
“…Apo-MT demonstrates robust affinity for Zn 2+ with an apparent stability constant at pH 7 of at least 10 11.2 [16]. Nevertheless it only removed 0–10% of Zn 2+ from the Zn-proteome (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of metal-thiolate clusters, relatively high solvent accessibility for at least some metal ions in the clusters, coupled with metal-dependent protein folding, leads to a peculiar combination of high thermodynamic stability with high kinetic lability -ideal prerequisites for intracellular zinc trafficking proteins. It is noted that the measurement of affinity constants of a protein with, e.g., 20 thiolate groups and seven metal binding sites is far from trivial, which might explain continuing disagreement about respective values, 189,190 even though there is overall agreement on the conclusion that free thiols from partially metallated MTs are present in vivo, and participate in zinc homeostasis. 191,192 The way to the first 3D structures for an MT was long and took at least one wrong turn: the first X-ray structure published was in fact incorrect, and it needed the advent of protein NMR spectroscopy to set the record straight.…”
Section: Intracellular Zinc Traffickingmentioning
confidence: 99%
“…22,29,30 Noncooperative metalation has been established for Zn 2+ , 31 Cd 2+ , 32−34 Bi 3+ , 35 and As 3+ . 22,29,30,36 Two recent papers 37,38 have discussed the binding of zinc to metallothionein and reported binding constants. The study by Namdarghanbari et al 37 using the zinc sensor FluoZin-3 reported that all the stability constants were approximately 10 11 and that there was no evidence of a stability constant as low as ∼10 8 that had been previously reported by Krezel and Maret.…”
mentioning
confidence: 99%